PENGARUH EKSTRAK ASYSTASIA GANGETICA TERHADAP PERTUMBUHAN AKAR ALLIUM CEPA - Naufal, Muhammad Ridha Naufal; Susintowati, Susintowati (BIO EDUCATIA JOURNAL, 2024)
Asystasia gangetica is a herbaceous plant commonly known as "ara sungsang," "rumput israel," and "Chinese violet." This plant is also referred to as an invasive species and is considered a weed. The purpose of this research is to study the effect of Asystasia gangetica extract on the root growth of Allium cepa. The research was conducted using an experimental approach with a completely randomized design (CRD), consisting of 6 treatments and 3 repetitions. The treatments of Asystasia gangetica extract administered included 0, 5, 25, 50, 75, and 100 ml/L. The observation parameter used was the number of growing shallot roots since shallot roots continue to grow each day to replace aging roots. Data analysis was performed using analysis of variance (ANOVA). The research results indicate that the application of Asystasia gangetica extract did not have a significant effect on the growth of Allium cepa roots. This suggests that Asystasia gangetica extract is suitable for promoting root growth at various concentrations. However, the results may vary if higher concentrations of the extract are used, potentially yielding different outcomes. The highest average growth of shallot roots was observed in the 100 ml/L treatment, at 21.6 roots. Based on these results, further research is needed to maximize the potential of Asystasia gangetica plant extract.